THE ANALYSIS OF GRAMMATICAL ERRORS ON STUDENTS’ ESSAY WRITING BY USING GRAMMARLY - Agustin, Ratna; Wulandari, Sri (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2022)
Considering the importance of grammar knowledge in the process of writing essays to students, the researchers aimed to research and explain the grammar errors in the essays of students of the English Department at UNISKA Kediri. The research study is classified into qualitative study. The study analyzed 14 samples English Essays written by UNISKA students. To classify the different types of errors made by students and identify common errors in writing student essays are using triangulation method. The results of this research found types of grammatical errors in the students' essays consist of 7 total errors in the grammar section, including 19,66% were found in articles a/an/the error, 13,68% were found in punctuation errors, 11,97% were found in plural/singular error, 11,97% were found in preposition errors, 5,13% were found in tenses error, 0,85% were found in to + V1 error, and 0,85% were found in pronoun error. Those errors indicated the problems faced by students in writing essays. The most dominant grammatical error found is in the articles a/an/the error including 19,66%. Researcher also found students’ difficulties facing in writing their essays. That found students' questionnaire answers. Researcher found the students’ difficulties are selecting and developing topic, write a well structured sentence and paragraph, grammar, and vocabulary. Based on the findings of grammar errors in student essays, the researcher hopes students to be more aware of writing essays with the correct grammar, aware of the wrong grammar on their Essays and using Grammarly Application to help in writing essays.